Bioethics. - Harding, Ben, producer/director/writer; Video Education Australasia (VEA, 2005)
Through case studies, this program looks at two aspects of bioethics, animals in medical research and genetically modified organisms (GMO's). The program explores some of the ethical issues involved in modern applications of biology and experts give their views for and against the two practices providing the viewer with an ethical debate